The Effect of Interval With The Ball Training Method and Fartlek Method on Increasing Vo2maks - alfin abdurahman; Hermanzoni - (Performa, 2019)
The problem with this research is that most of the endurance (VO2maks) players are in the low category. This is known from the race activities carried out by the SSB Muspan soccer team. This study aims to determine the effect of interval training with the ball and fartlek training on increasing VO2Maks. This type of research is a quasi-experimental sampling technique in this study using purporsive sampling. The number of samples in this study were 20 people. The research instrument used to measure VO2Maks in this study used the Multistage Fitness Test. The results of data analysis there is the effect of interval training with the ball on increasing VO2Maks, there is the effect of fartlek training on increasing VO2Max, there is a significant effect of interval training with the ball and fartlek training on increasing VO2Max. Thus it can be concluded that interval training with the ball and fartlek training have a significant effect on increasing VO2Maks capacity